Religious Ideology Dissemination And Contestation In Indonesian Islamic Educational Institutions - Junaidi, Junaidi; Afrinaldi, Afrinaldi; Artika, Febria Sri; Al-Momani, Mohammad Omar (Universitas Islam Negeri Mataram, 2024)
Islamic education in Indonesia is currently in the spotlight due to rivalries among Islamic groups that have turned educational institutions into battlegrounds. This study aimed to identify the process of spreading religious ideology in educational institutions, analyze its educational aspects, and explore the implications of competition among religious groups. This study employed a qualitative approach with phenomenological and sociological research designs. The data sources were collected from school administrators, teachers, students, and stakeholders. In-depth interviews, observation, and documentation were used to gather data in three different locations: Aceh, West Sumatra, and Yogyakarta. The results show that educational institutions spread religious ideology through classroom learning activities, subjects, and books. In addition, the spread of ideology also occurs through religious rituals, extracurricular activities, school policies, and culture. The spread of ideology has implications for the emergence of diverse religious understandings in students and different religious identities between groups. It creates a depth of ideological differences in society. Ideological rivalry in Islamic education in Indonesia is a significant challenge that needs to be addressed to ensure quality education that supports the holistic development of individuals and society.